The Effect of MSME Development Programs on the Growth of Women's Enterprises in West Nusa Tenggara - Muhammad Taufik; Sari Restapa (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study is to assess the impact of Micro, Small, and Medium Enterprises (MSME) development programs provided by the Indonesian government on the business development of women entrepreneurs in West Nusa Tenggara (NTB). To answer this question, we distributed online questionnaires to women entrepreneurs in NTB to see how involved they were in these programs and how well these programs had an impact on their business development. After receiving responses from 303 respondents, the results of this study indicated that these programs had less impact on their business development. This is due to the lack of information that respondents receive about these programs so they do not have the opportunity to participate. On the other hand, respondents who had participated in several programs confirmed that the programs they had participated in had a good impact on their business development. This study offers valuable insights into the business conditions of women in NTB and sheds light on the obstacles they encounter. As a result, the research's outcomes are expected to provide valuable recommendations to the government for the formulation of future programs that facilitate the growth of women entrepreneurs in Indonesia, particularly in NTB.